Pelatihan Penulisan Artikel Ilmiah bagi Guru dengan Memanfaatkan Aplikasi Scite AI - Nasrul; Maru, Rosmini; Haris; Arfandi; Amdah, Misdar (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
One of the benchmarks for determining whether a teacher is capable of critical thinking is their ability to write scientific articles well. Through scientific writing, teachers are required to think critically, logically, systematically, and analytically to find solutions to the problems they face. Currently, there are still few teachers who can write articles well, especially teachers at UPT SDN 186 Taluma. Therefore, the objective of this training is to enhance teachers' skills and abilities in writing high-quality scientific articles and to understand how to utilize AI technology in their research. The methods used in this training include theoretical sessions, demonstrations of the Scite AI application, and hands-on practice in writing scientific articles with instructor guidance. The results of this training show that participants experienced significant improvements in understanding the structure and key elements of scientific articles, as well as their ability to integrate relevant scientific sources through the Scite AI application. Participants also reported improved effectiveness and ease in composing scientific articles using the Scite AI application. In conclusion, this training was effective in enhancing teachers' scientific writing skills and demonstrated the significant potential of the Scite AI application as a tool for academic writing and research.